1987
DOI: 10.1177/0310057x8701500209
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic-Related Recovery Room Complications

Abstract: A prospective survey was conducted over a one-month period in all surgical patients admitted to the recovery room of a university-affiliated teaching hospital. Complications arising in the recovery room were documented by the nursing staff according to predefined criteria and were critically evaluated. A total of 443 patients were admitted to the recovery room and in 133 (30%) of these, some form of complication was noted. There were 86 patients with complications referable to the central nervous system, 68 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 26 publications
0
33
1
2
Order By: Relevance
“…This frequency is considered high when compared with the complication rate associated with other surgery, which range from 10% to 30%. 6,19 The number of patients undergoing pharyngeal flap surgery was high at the authors' institution (2299 procedures). Two reasons that account for this are the length of time covered by the study and that the institution is a referral center for the treatment of craniofacial anomalies in Latin America.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This frequency is considered high when compared with the complication rate associated with other surgery, which range from 10% to 30%. 6,19 The number of patients undergoing pharyngeal flap surgery was high at the authors' institution (2299 procedures). Two reasons that account for this are the length of time covered by the study and that the institution is a referral center for the treatment of craniofacial anomalies in Latin America.…”
Section: Discussionmentioning
confidence: 95%
“…In relation to hemodynamic complications, other studies have reported rates ranging from 3% to 55% 14,19 . The incidence of pain observed in this study (14%) was lower than those reported in other studies (20-75%) 5,20 .…”
Section: Discussionmentioning
confidence: 97%
“…[23] The rate of re-intubation in neurosurgical patients is found to be between 0.17% and 0.83%. [101112] Vidotto and colleagues retrospectively studied the outcome of elective craniotomy patients who were re-intubated within 48 hrs of a planned extubation and reported a re-intubation rate of 16%. [3] Patients who were on mechanical ventilation for up to six hrs after surgery were included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Zelcer and Wells[3] found a 9% incidence of unresponsiveness at the end of 15 min after general anaesthesia among 443 mixed surgical patients. Arousal beyond 15 min[3] and 30 min[4] is labelled as delayed emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Zelcer and Wells[3] found a 9% incidence of unresponsiveness at the end of 15 min after general anaesthesia among 443 mixed surgical patients. Arousal beyond 15 min[3] and 30 min[4] is labelled as delayed emergence. Residual anaesthesia may either give the false impression of a neurological deficit[5] or prevent the early diagnosis of a developing intracranial lesion like haematoma, herniation and cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%